Exploration on the Research Progress of Traditional Chinese Medicine in Treating Uremic Cardiomyopathy based on Cardiomyocyte Protection - Yao, Ximeng; Li, Xiaohui; Chen, Liming; Qu, Jie (Journal of Contemporary Medical Practice, 2025)
Uremic cardiomyopathy is an important complication that affects the quality of life and prognosis of patients with chronic kidney disease. The damage to myocardial cells is a major pathological mechanism of uremic cardiomyopathy. Traditional Chinese medicine (TCM) can promote the elimination of uremic toxins, improve the renal and cardiac function of chronic kidney disease patients, and alleviate renal anemia. At the same time, TCM can regulate relevant signaling pathways and gene expressions through multiple targets, reduce oxidative stress and inflammatory responses in myocardial cells, inhibit apoptosis of myocardial cells, and improve left ventricular hypertrophy and myocardial fibrosis. This ultimately enhances cardiac function and delays the progression of uremic patients and the development of uremic cardiomyopathy. In this paper, the author aims to review recent experimental research advances in TCM for the treatment of uremic cardiomyopathy from the perspective of protecting damaged myocardial cells. The goal is to explore the strategies and methods of TCM in treating uremic cardiomyopathy, providing references and evidence for clinical TCM treatment of this condition.